2018
DOI: 10.14710/jksa.21.4.224-231
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Characterization of Oyster Shell as Chitosan and Nanochitosan

Abstract: Oyster is one of bivalve groups widely consumed by human, thus, it results in producing huge waste shells affecting the environment. One way to increase the value of oyster shells is to process them into chitosan. This study aims to isolate chitin then synthesize it into chitosan and convert chitosan into nano-sized chitosan and analyze the characteristics. The steps to produce chitosan from waste shells included demineralization using HCl 1 N and deproteinization using NaOH 3%. The next step was to convert ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
2
6
0
9
Order By: Relevance
“…It can be seen from Figure 2, that the peaks formed for POS are at wave number 3428.28 cm-1 indicating the presence of amine groups (-NH 2 ). Similar to the previous studies conducted, at the peak of 3363 cm -1 and 1639 cm -1 (Ghafar, Hussein, & Zakaria, 2017) 3399 cm -1 and 1686.28 cm -1 (Handayani, Syahputra, & Astuti, 2018) representing the amine functional group, and all analyzed samples have absorption peaks due to amide (NH) and widening peaks which is caused by the O-H group at wave number 2517-2513 cm -1. But the COS-800 has the most typical and better amide absorption band compared to the others.…”
Section: Results and Discussion Analysis Of Ftirsupporting
confidence: 84%
See 1 more Smart Citation
“…It can be seen from Figure 2, that the peaks formed for POS are at wave number 3428.28 cm-1 indicating the presence of amine groups (-NH 2 ). Similar to the previous studies conducted, at the peak of 3363 cm -1 and 1639 cm -1 (Ghafar, Hussein, & Zakaria, 2017) 3399 cm -1 and 1686.28 cm -1 (Handayani, Syahputra, & Astuti, 2018) representing the amine functional group, and all analyzed samples have absorption peaks due to amide (NH) and widening peaks which is caused by the O-H group at wave number 2517-2513 cm -1. But the COS-800 has the most typical and better amide absorption band compared to the others.…”
Section: Results and Discussion Analysis Of Ftirsupporting
confidence: 84%
“…The samples analyzed all come from oyster shells containing silica, causing the formation of absorption peaks at wave numbers 877-712 cm -1 , this indicates that the SiO 2 contained in POS, COS and Zn-AOS has not been lost. Similar to previous studies conducted, at the peak of 871 cm -1 , there was an absorption caused by silica (Handayani et al, 2018). The silica content is one of the impurities for adsorbents that can fill the pores, so the ability of adsorption is reduced.…”
Section: Results and Discussion Analysis Of Ftirsupporting
confidence: 84%
“…Kalsium yang berasal dari hewan seperti limbah tulang sampai saat ini belum dimanfaatkan untuk kebutuhan manusia, tulang ikan salah satu limbah industri perikanan yang memiliki kandungan kalsium terbanyak diantara bagian tubuh ikan, karena unsur pertama dari tulang ikan adalah kalsium, fosfor, dan karbonat serta mudah diperoleh dan memiliki nilai yang ekonomis. Limbahlimbah perikanan selain dapat dimanfaatkan sebagai kitosan (Handayani et al, 2018) juga dapat dimanfaatkan sebagai sumber gelatin (Moranda et al, 2018;Rosida et al, 2018). Pemanfaatan limbah tulang ikan kambing-kambing sebagai sumber kalsium juga telah dilakukan menggunakan metode thermal decomposition (Restari et al, 2019).…”
unclassified
“…The result of the XRF analysis was shown in table 2. In table 2, each sample was consist of calcium as the main compound which following the previous result which reported that the oyster shell had similar calcium properties with clams shell (Handayani, L & Syahputra, F. 2018). The calcium compound was derived from the CaO compound formed from the decomposition of CaCO 3 at high temperatures during the physical calcination process.…”
Section: X-ray Fluorescence (Xrf) Analysismentioning
confidence: 87%
“…Several studies have been reported in the utilization of oyster shells as the source of Calcium (Handayani & Syahputra, 2017) and Chitosan (Handayani, Syahputra, & Astuti, 2018) or converting as adsorbent (Afranita, Anita, & Hanifah, 2014;Daud et al, 2017;Jung, Lee, Lee, Yoo, & Shon, 2007;Nasution & Iriany, 2015). Afranita (2014) reported the adsorption capacity of clams shells in which it can absorb 53.11% of 30 ppm per hour of Tin ions (Afranita et al, 2014).…”
Section: Introductionmentioning
confidence: 99%